A Correlation between Medication Adherence and Blood Glucose Levels in Patients with Type II Diabetes Mellitus at Sawah Lebar Health Center, Bengkulu City in 2025 - Annisa Annisa; Delta Aprianti; Sasteri Yulianti (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Type II Diabetes Mellitus is a chronic disease that requires long-term management, one of which is medication adherence to maintain controlled blood glucose levels. Non-adherence to antidiabetic medication may lead to uncontrolled blood glucose levels and increase the risk of complications. This study aims to determine a correlation between medication adherence and blood glucose levels in patients with Type II Diabetes Mellitus at Sawah Lebar Health Center, Bengkulu City in 2025. This study employed a quantitative correlational design with a cross-sectional approach. Medication adherence was measured using the Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire, while blood glucose levels were measured through Random Blood Glucose (RBG) examination using a glucometer. The population of this study consisted of all patients with Type II Diabetes Mellitus receiving treatment at Sawah Lebar Health Center, with a total sample of 49 respondents. The results showed that most respondents had a moderate level of medication adherence, accounting for 21 respondents (42.9%). Based on the results of random blood glucose examinations, the majority of respondents had abnormal (high) blood glucose levels, totaling 35 respondents (71.4%). The statistical analysis using the Chi-Square test showed a p-value of 0.000 (p < 0.05), indicating a significant correlation between medication adherence and blood glucose levels among patients with Type II Diabetes Mellitus at Sawah Lebar Health Center, Bengkulu City in 2025. The researchers recommend that the Health Center use the findings of this study as a reference to improve healthcare service programs, particularly in enhancing medication adherence to support normal blood glucose levels among patients with Type II Diabetes Mellitus